Assessing Skills and Capacity for Informatics: Activities Most Commonly Performed by or for Local Health Departments. (November 2016) - Drezner, Kate; McKeown, Lisa; Shah, Gulzar H.
Abstract : Objective: To describe the informatics activities performed by and for local health departments. Design: Analysis of data from the 2015 Informatics Capacity and Needs Assessment Survey of local health departments conducted by the Jiann-Ping Hsu College of Public Health at Georgia Southern University in collaboration with the National Association of County & City Health Officials. Participants: 324 local health departments. Main Outcome Measure(s): Informatics activities performed at or for local health departments in use and analysis of data, system design, and routine use of information systems. Results: A majority of local health departments extract data from information systems (69.5%) and use and interpret quantitative (66.4%) and qualitative (55.1%) data. Almost half use geographic information systems (45.0%) or statistical or other analytical software (39.7%). Local health departments were less likely to perform project management (35.8%), business process analysis and redesign (24.0%), and developing requirements for informatics system development (19.7%). Local health departments were most likely to maintain or modify content of a Web site (72.1%). A third of local health departments (35.8%) reported acting as "super users" for their information systems. A significantly higher proportion of local health departments serving larger jurisdictions (500 000+) and those with shared governance reported conducting informatics activities. Conclusion: Most local health department informatics activities are completed by local health department staff within each department or a central department, but many state health departments also contribute to informatics at the local level. Larger local health departments and those with shared governance were more likely to perform informatics activities. Local health departments need effective leadership, a skilled workforce, strong partnerships, and policies that foster implementation of health information systems to successfully engage in informatics. Local health departments also face important training needs, including data analytics, project management, and geographical information systems, so they can adapt to the increasing availability of electronic data and changes in technology. Abstract : This article describes the informatics activities performed by and for local health departments.